The application of nitric oxide to control biofouling of membrane bioreactors - Rice, Scott A. (2015)
A novel strategy to control membrane bioreactor (MBR) biofouling using the nitric oxide (NO) donor compound PROLI NONOate was examined. When the biofilm was pre-established on membranes at transmembrane pressure (TMP) of 88–90 kPa, backwashing of the membrane module with 80 μM PROLI NONOate for 45 min once daily for 37 days reduced the fouling resistance (Rf) by 56%. Similarly, a daily, 1 h exposure of the membrane to 80 μM PROLI NONOate from the commencement of MBR operation for 85 days resulted in reduction of the TMP and Rf by 32.3% and 28.2%. The microbial community in the control MBR was observed to change from days 71 to 85, which correlates with the rapid TMP increase. Interestingly, NO-treated biofilms at 85 days had a higher similarity with the control biofilms at 71 days relative to the control biofilms at 85 days, indicating that the NO treatment delayed the development of biofilm bacterial community. Despite this difference, sequence analysis indicated that NO treatment did not result in a significant shift in the dominant fouling species. Confocal microscopy revealed that the biomass of biopolymers and microorganisms in biofilms were all reduced on the PROLI NONOate-treated membranes, where there were reductions of 37.7% for proteins and 66.7% for microbial cells, which correlates with the reduction in TMP. These results suggest that NO treatment could be a promising strategy to control biofouling in MBRs.